Influential and Worthy: A Video-centric Exploration of Travel Influencers’ Value Chain Logic - Guo, Siqi; Deng, Ning; He, Zeya (Journal of travel research, 2025)
Influencer marketing has ushered in a new mode of electronic commerce, necessitating research to explore this emerging business logic. This study, grounded in communication and persuasion theory, develops a theoretical framework of travel influencers’ value chain logic. It elucidates how these influencers’ communication strategies drive their audience members’ online engagement and influencers’ business value on short video platforms. A multi-method design and video-centric approach revealed three dimensions of influencers’ communication strategies—physical attractiveness, content richness, and social activity—that significantly shaped audience members’ online engagement with the content. Such engagement in turn had a positive impact on influencers’ business value. These findings help to clarify value chain logic in influencer marketing and carry managerial implications for influencers and travel brands.